2009
DOI: 10.1128/jb.00652-09
|View full text |Cite|
|
Sign up to set email alerts
|

Facilitated Oligomerization of Mycobacterial GroEL: Evidence for Phosphorylation-Mediated Oligomerization

Abstract: The distinctive feature of the GroES-GroEL chaperonin system in mediating protein folding lies in its ability to exist in a tetradecameric state, form a central cavity, and encapsulate the substrate via the GroES lid. However, recombinant GroELs of Mycobacterium tuberculosis are unable to act as effective molecular chaperones when expressed in Escherichia coli. We demonstrate here that the inability of M. tuberculosis GroEL1 to act as a functional chaperone in E. coli can be alleviated by facilitated oligomeri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
58
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 42 publications
(59 citation statements)
references
References 65 publications
0
58
1
Order By: Relevance
“…While GroEL1 has been functionally characterized in these studies, the ability of GroEL2 in complementing E. coli GroEL was studied independently by two groups, which resulted in an understanding that GroEL2 can functionally replace E. coli GroEL in vivo and in vitro only upon abundance (Hu et al 2008;Kumar et al 2009;Fan et al 2012). Moreover, GroEL2 has been shown to localize at the cell wall (Hickey et al 2009) as a multimer and upon cleavage by a serine protease, Hip1, separates into the secretion-competent monomeric form.…”
Section: Multiple Groels In Mycobacteriamentioning
confidence: 99%
See 3 more Smart Citations
“…While GroEL1 has been functionally characterized in these studies, the ability of GroEL2 in complementing E. coli GroEL was studied independently by two groups, which resulted in an understanding that GroEL2 can functionally replace E. coli GroEL in vivo and in vitro only upon abundance (Hu et al 2008;Kumar et al 2009;Fan et al 2012). Moreover, GroEL2 has been shown to localize at the cell wall (Hickey et al 2009) as a multimer and upon cleavage by a serine protease, Hip1, separates into the secretion-competent monomeric form.…”
Section: Multiple Groels In Mycobacteriamentioning
confidence: 99%
“…Furthermore, evolutionary studies on Mtb groEL sequences have suggested rapid evolution of the groEL1 gene (Goyal et al 2006) and that the difference in the rates of evolution between GroEL1 and GroEL2 has been proposed to be due to differential interaction of these chaperonins with the host immune system (Hughes 1993). Although these studies have principally employed biochemical tools on purified proteins and convincingly demonstrated the inability of Mtb GroELs to act as chaperones, further genetic studies on these chaperonin genes have provided evidence towards the hypothesis that Mtb GroELs are inactive as chaperonins (Kumar et al 2009;Henderson et al 2010;Kumar and Mande 2011). Phenotypic investigations on the Mtb GroELs in different E. coli groEL mutant strains established that Mtb GroELs are ineffective in complementing E. coli GroEL (Kumar et al 2009).…”
Section: Multiple Groels In Mycobacteriamentioning
confidence: 99%
See 2 more Smart Citations
“…However, the tetradecamer of one of the GroELs, Cpn60.1, has been detected in cell extracts. 32) The tetradecameric form is phosphorylated while the heptameric form is not, indicating phosphorylation-mediated regulation of the GroEL oligomeric states. The GroELs possess very weak ATPase activity.…”
Section: Discussionmentioning
confidence: 99%